Evaluating the outcomes of VCA-led improvement projects: A case study of an Australian prawn fishery. Issue 12 (5th December 2016) - Johns, Craig Michael; Kimber, Nathan; Howieson, Janet; Lawley, Meredith
Abstract : Purpose: The purpose of this paper is to describe the potential benefits of value chain analysis (VCA) improvement projects by evaluating their effectiveness for all chain members. Design/methodology/approach: The study uses an action research approach to extend VCA methodology by implementing an improvement project developed through the VCA process, and the subsequent evaluation of this project using a combination of techniques. Findings: The paper addressed a key research gap around the evaluation of improvement projects and has shown that the implementation of VCA, both as a guiding framework for developing interventions and a basis for evaluating their effectiveness, can provide significant benefits to all industry stakeholders. Research limitations/implications: The research focussed on evaluating the outcomes of a single project within an industry case study. While the diversity in different industry structures and the range of improvement projects possible makes it difficult to generalise the findings, the methodology and evaluation options make a valuable practical and theoretical contribution. Practical implications: The case study highlights the advantages of improvement projects guided by VCA and offers a variety of evaluation options for both private and public sector VCA practitioners. Originality/value: This study is one of the very few to evaluate the implementation of activities identified during the diagnostic phase of an agribusiness VCA.